Dürer's lost masterpiece art and society at the dawn of a global world - Rublack, Ulinka 1967- (Oxford University Press, 2023)
This volume tracks the history of a turning point in the career of the celebrated German artist Albrecht Dürer (1471-1528), when he stopped painting altarpieces after arguing with a merchant patron over payment. As an eloquent homage to Dürer's life, it brings us closer to the creation and meaning of his paintings than ever before
Also issued in print: 2023. - Includes bibliographical references and index
Keywords: Dürer, Albrecht / 1471-1528 / Assumption of the Virgin and her coronation by the Holy Trinity; Dürer, Albrecht / 1471-1528; Heller, Jakob / approximately 1460-1522; Heller, Jakob; Dürer, Albrecht -- 1471-1528; Geschichte 1470-1650; Art and Design / ukslc; Fine arts: treatments & subjects / thema; Heller Altarpiece (Panel painting); Altarblatt; Kulturaustausch; Auftraggeber; Handel; Kunsthandel; Sammlung; Kunst; Globalisierung